The importance of the role of financial analysis in making investment decisions in securities - Case Study: Khartoum Stock Exchange - Ahmed, Waleed Alsayed Almahdi (Journal of Economic, Administrative and Legal Sciences, 2021)
This research aimed at the followings: Identifying the important role of financial analysis depending on information cited on financial statements and reports in making the right investment decision in Khartoum Stock Exchange. Adopting a reliable financial analysis that can assist to analyze and evaluate the financial and non-financial information to make decisions of buying، selling or reserving stocks with rational investment decisions at Khartoum Stock Exchange. In order to discuss the research problem، the researcher tests the hypotheses: The rational financial analysis is considered an effective tool in making a good investment decision, the accounting information helps investors in stock markets in making the right investment decision. The research adopts the deductive methodology to formulate the research problem and hypotheses; the inductive method to collect data from primary and secondary sources; the historical method to tackle the previous studies; whereas the analytical-descriptive method to test the validity of the hypotheses. The important results of the research could be summarized as Adopting modern financial analysis techniques provide information that help in making the right investment decisions Failure to make the rational investment decision is related to inefficiency of the information and financial reports depended upon in each stage of making investment decision and Whereas the most important recommendations are to adopt modern techniques in analyzing financial statements by using SPSS. Provide sufficient information about stock exchange rates and dealings regularly on the internet websites and workshop papers.